2017
DOI: 10.1158/1535-7163.mct-16-0383
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oncolytic Activities of the Telomerase-Specific Replication-Competent Adenovirus Expressing Short-Hairpin RNA against Dicer

Abstract: Oncolytic viruses have been receiving much attention as potential agents for cancer treatment. Among the various types of oncolytic viruses, the telomerase-specific replication-competent adenovirus (TRAD), which carries the tumor-specific promoter-driven E1 gene expression cassette, exhibits efficient antitumor effects. The development of a novel TRAD that shows higher replication efficiency and antitumor activity would be highly beneficial for safer and more efficient cancer therapy. We recently demonstrated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Finally, how LAMP5 might be suppressed in a therapeutic setting should also be considered for further translational application. Based on recent progress in oncolytic viruses (47)(48)(49)(50), using an adenovirusmediated short hairpin RNA delivery system containing shRNA targeting LAMP5 or CRISPR-Cas9 containing sgRNA targeting LAMP5 may be an alternative method for suppressing LAMP5 in future clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, how LAMP5 might be suppressed in a therapeutic setting should also be considered for further translational application. Based on recent progress in oncolytic viruses (47)(48)(49)(50), using an adenovirusmediated short hairpin RNA delivery system containing shRNA targeting LAMP5 or CRISPR-Cas9 containing sgRNA targeting LAMP5 may be an alternative method for suppressing LAMP5 in future clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to examine whether Ad infection is regulated by miRNA-mediated posttranscriptional silencing and to identify miRNAs and their target genes involved in Ad infection. Our previous studies demonstrated that Dicer-mediated cleavage of Ad-encoded small noncoding RNAs (VA-RNAs) negatively regulated Ad replication and that Dicer knockdown led to the promotion of Ad replication (28,44). In addition, knockdown of Ago2, which is a major component of the RISC, also promoted Ad replication, although the HeLa cells were pretreated with PD0332991 at 1 M, followed by infection with WT-Ad at 100 VP/cell.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible to improve oncolytic Ad by incorporation of a short-hairpin RNA which functions to downregulate Dicer (an endoribonuclease which has a role in processing virus-associated RNA). Downregulation of this protein inhibits the destruction of viral RNA and allows Ad to replicate efficiently and therefore improves the efficacy of this OV ( 54 ).…”
Section: Adenovirusmentioning
confidence: 99%